1996
DOI: 10.1007/bf02280992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-10 on collagen-induced arthritis in mice

Abstract: Abstract. In the present study we investigated the effect of a potent anti-inflammatory cytokine, interleukin (IL)-10, on the development of collagen-induced arthritis (CIA) in mice. Each DBA1/J mouse was immunized with 200 gg of native collagen and followed by booster injections at 3 weeks, rmIL-10 was injected i.p. daily at a dose of 100ng/mouse. Mice were divided into four groups according to the administration period of rmIL-10. As a result, a 48-day course of IL-10 treatment significantly suppressed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 30 publications
4
40
1
Order By: Relevance
“…It has been reported that there was an increase in the IgG1:IgG2a ratio after injection of vIL-10-expressing vectors (17), and a decrease in total anti-CII IgG was observed after repeated high doses of murine rIL-10 in rats (14). However, others did not see any such effects when using similar systems (15,16,18,58,60). These discrepancies could perhaps be explained by the dose and timing of IL-10 treatment, indicating that much more effort must be put in to investigate how variations in IL-10 levels affect different functions of the immune system.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that there was an increase in the IgG1:IgG2a ratio after injection of vIL-10-expressing vectors (17), and a decrease in total anti-CII IgG was observed after repeated high doses of murine rIL-10 in rats (14). However, others did not see any such effects when using similar systems (15,16,18,58,60). These discrepancies could perhaps be explained by the dose and timing of IL-10 treatment, indicating that much more effort must be put in to investigate how variations in IL-10 levels affect different functions of the immune system.…”
Section: Discussionmentioning
confidence: 97%
“…Several lines of evidence suggest that GLAST and GLT-1 are the predominant GTs and are responsible for clearing synaptic glutamate and preventing excitotoxicity (Tanaka et al, 1996;Robinson and Dowd, 1997). Previous study has shown that many regulatory factors, such as dibutyryl cAMP, epidermal growth factor, and pituitary adenylate cyclase-activating polypeptide, modulate GLAST and GLT-1 mRNA levels (Zelenaia and Robinson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, their precise roles are, as yet, incompletely defined. A growing body of evidence from both animal models of arthritis and human RA suggests that Th2-type cytokines, such as IL-4 and IL-10, can protect against arthritis, whereas Th1-type cytokines, such as IL-2 and IFN-␥, can be pro-inflammatory (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Heterogeneous Effects Of Il-2 Onmentioning
confidence: 99%